Просторова реконструкція нюхових структур Lacerta viridis за допомогою комп’ютерного моделювання - Титюк, Ольга; Грубий, Володимир; Степанюк, Ярослав; Яригін, Олександр; Tityuk, Olga; Grubiy, Volodymyr; Stepanyuk, Yaroslav; Yaryhin, Oleksandr (Східноєвропейський національний університет імені Лесі Українки, 2015)
Описано приклад створення просторової реконструкції структур нюхового аналізатора (носової порожнини, вомероназального органа, нюхових нервів, нюхових цибулин) ембріона ящірки зеленої Lacerta viridis 34-ї стадії розвитку. Побудову просторової моделі проведено в програмі Amira 5.0. The example of creation of olfactory analyzer’s spatial reconstruction (nasal cavity, vomeronasal organ, olfactory nerves, olfactory bulbi) of European green lizard’s embryo at the 34th stage of development is described. Construction of three-dimensional model in the program Amira 5,0. is done on the basis of photos of serial histological sections. The work in the program consists of preparing of microphotos, levelling of structures under investigation, picking out the contours and creation of three-dimensional model. Doing spatial reconstruction with the help of Amira doesn’t demand great time consumption and special training and is suited for all biological objects. The spatial model of lizard’s embryo which was created exactly reflects all morphological particularities of olfactory elements. This model is easy to use, it allows to see and to describe all morphological structures.
Spatial Reconstruction of Olfactory Structures Lacerta viridis by Means of Computer Simulation
Keywords: ембріон; просторова реконструкція; нюховий епітелій; вомероназальний орган; embryo; spatial reconstruction; olfactory epithelium; vomeronasal organ